Elucidating the role of nano boron and zinc oxide-coated silane-treated cellulose nanocrystals (CNCs) on the mechanical, thermal, and flammability characteristics of high-density polyethylene (HDPE) - Amirmohammad Raeisi; Ismat Ara; Greg Holt; Nicole Stark; Dilpreet S. Bajwa (Nano Trends)
The fire risk of synthetic polymers has emerged as a growing safety issue. High-density polyethylene (HDPE) is one of the most used polymers in different applications. However, HDPE has some drawbacks, such as low thermal and mechanical properties. To address this challenge, silane-functionalized cellulose nanocrystals (CNCs), nano boron oxide (B2O3) and nano zinc oxide (ZnO) were incorporated into the HDPE matrix in different percentages (3 %, and 5 %) and weight ratios (1:1, and 1:2). The CNCs were surface modified through silanization process to enhance dispersion and interfacial bonding, while metal oxides were introduced to improve thermal stability and flame retardancy. The composites were characterized using scanning electron microscopy (SEM), dynamic mechanical analyzer (DMA), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analyzer (TGA), horizontal burn test, and microcalorimetry tests. The results indicated that adding CNCs-ZnO resulted in a 64 % increase in mechanical properties, a 28 % decrease in weight loss, and a reduced flame spread rate of the composites. The CNCs- B2O3 composites showed a lower flame spread rate and a 52 % improvement in mechanical properties. Overall, adding nano metallic fillers, such as nano ZnO and B2O3, significantly enhanced HDPE composites' thermal stability, mechanical properties, and fire resistance. These improvements highlight the potential of nano metal oxides and CNC as functional fillers where mechanical strength and fire safety are essential.